Determination of microbiological and physicochemical characteristics of sweet sorghum and wort on its base in the non-alcoholic drinks technology - Korolenko, A.; Karputina, Margarita; Khargeliia (Karputina), Daria; Teterina, Svitlana (My University, 2014)
The paper identified the quantitative and qualitative composition of microflora and basic physical and chemical properties of sugarsorghum juice, diluted apple concentrate and mash on them. The samples wort for physico-chemical parameters recommended for use intechnology fermented soft drinks.The use of technology fermented beverages mash of soft thermal processingof sorghum juice and sugar mixture 70% nepidkyslenoho and unpasteurized juice mash of sorghum and sugar 30% diluted apple cider for quality and safe products.
Keywords: wort; the sweet sorghum juice; fermented soft drinks; ферментовані безалкогольні напої; сок цукрового сорго; сусло; ферментированные безалкогольные напитки; сок сахарного сорго; кафедра технології оздоровчих продуктів; кафедра біотехнології і мікробіології; кафедра біотехнології продуктів бродіння і виноробства